High performance multiple passband substrate integrated plasmonic filters - Ye, Longfang; Chen, Zhongkai; Zhang, Yong; Li, Weiwen; Zhang, Yao; Wei, Kanglin (IEEE transactions on circuits and systems. II, Express briefs, 2023)
We proposed a new variety of substrate integrated plasmonic filters (SIPFs) with multiple passband characteristics based on the concept of spoof surface plasmon polaritons (SSPPs). By etching a periodic interdigital structure array on the top metal layer of substrate integrated waveguide (SIW), we can achieve high-efficiency microwave SSPP transmission with an insertion loss of 1 dB in the passband of 7.4-12.5 GHz, and a high rejection level of 27 dB in the rejection bands. By introducing antisymmetric C-ring resonators (ASCRs) in the filter structure, the passband number and bandwidth of the filter can be flexibly manipulated. To validate the proposed design, four SSPP filters prototypes are fabricated and tested, showing good filtering performances with a high transmission coefficient (S21>-1 dB) and low reflection coefficient (S11 < -12 dB) in their passbands, and a high rejection level over 15 dB between them. By changing the geometric parameters of ASCR, the number of passbands can be increased from 1 to 3, and the passband center frequency and bandwidth can be engineered accordingly. The proposed SSPP filters with good multiple passband characteristics may have great potential applications in microwave wireless integrated plasmonic circuits and communication systems.